Main trends of the international market of educational services - T. I. Chinaeva (Статистика и экономика)
The world education system everything will more be transformed to the multi-billion industry, one of the profitable directions of which is training of foreign students. Creation and development of successfully functioning system of the international education, attraction of a significant amount of foreign students are not only to increase the budget of higher education institution and to lift its prestige, but also and a method of promotion of policy, culture, economy, a conduct of life of the host country home. With respect there to research and practical interest has studying and the analysis of the main directions of development of the international market of educational services. This article in which changes of the main indicators reflecting the main vectors of export of education in the leading countries - exporters and in our country are considered is also devoted to these questions.The purpose of work is the analysis of development of the international market of educational services in recent years. The analysis of analytical and statistical information on the processes happening in this area, both at the international level, and in Russia is the basis.In the course of the research the methods of the analytical and logical analysis on the basis of statistical data promoting more detailed studying of dynamic and structural changes of the social and economic phenomena and processes were used.In general for the last 30 years the extent of the international student’s mobility increased more than by 6 times. The international educational market constantly develops, increasing the turnover. However flows of the international students periodically change the orientation, both on countries of source, and over the countries of training. At the same time it is possible to note that changes in structure of the largest countries recipients happen more slowly, than as a part of the countries delivering foreign students. The largest world sources of the international students are such countries now as: India, China, Korea. It is also possible to note, despite certain efforts of the Russian higher education institutions on involvement of foreign students, country line items in the global market of educational services aren’t high. The carried-out analysis allowed to reveal a number of the main a tendency of development of the international market of educational services among which to the main treat the growing demand for receipt of the higher education outside the country, the amplifying competition for involvement of foreign students in higher education institutions and shift from mass set of students more selective set of talented youth.